Implementasi Nilai-Nilai Akhlak Terhadap Pemuda Masjid Dalam Perspektif Pendidikan Islam - Tyas Ajeng Choirunisaa (Islah Tarbawi: Journal of Islamic Education and Learning, 2025)
Moral values in Islamic education, especially morality, are only limited to knowledge and insight without being based on the implementation of the values contained in these morals, especially when it comes to mosque youth who should provide examples or color the surrounding environment by imitating them. The research method in this case uses techniques descriptive qualitative analysis with data reduction analysis techniques, data presentation, drawing/conclusion and verification, so that youth and the surrounding environment can get used to carrying out worship on time and in congregation, getting used to throwing garbage in its place, Spontaneous ant operations (picking up trash), getting used to reprimand/overcoming disagreements / quarrels / bad things, getting used to saving energy, getting used to the culture of queuing, getting used to preserving the environment, giving examples of neat / simple clothes, giving examples of coming on time, giving examples of going home on time / according to the schedule for going home, giving examples of simple life, giving examples of speaking politely and politely, giving examples of honest behavior and giving examples of praising good work.